Aging and thriving with HIV: a photovoice project with long-term HIV survivors in Miami, Florida. Issue 3 (2nd September 2021) - Witkowski, Kaila; Valerio, Reyni; Samad, Abdul; Matiz-Reyes, Armando; Padilla, Mark
ABSTRACT: Background: Long-term survivors of HIV in Miami, Florida are facing critical health and social issues as they age with this disease. Methods: Using PhotoVoice methodology, nine Latino/a activist-artists were recruited to take pictures depicting their everyday life-challenges to be used in several photography exhibits aimed at informing local policy direction. Results: The group identified a positive approach to aging with HIV as a priority at the individual, community and policy level, emphasizing policy alternatives to the negative and disease-ridden stereotypes that embed current discussions on living and aging with HIV. The activists highlight specific community and policy solutions that respond to the growing needs of long-term survivors of HIV/AIDS among Latino communities in South Florida. Conclusions: The findings suggest that Miami (and areas with a large HIV-positive population) may benefit from community and policy solutions that take a successful aging approach and build upon the resiliency of this population.